Sustainability in the Supply Chain: Conditions and Mechanisms for Waste Management in Medium-Sized Retail Supermarkets - Matias, Alano Nogueira; Pereira, Alonso Luiz (International Journal of Advanced Engineering Research and Science, 2022)
In view of legal and social requirements, sustainability became the core of the actions and actions of associations in adopting policies to reduce environmental damage with benefits to society. This study aims to analyze the relationship between waste management practices and the generation of value in medium-sized retail supermarkets. A research is justified by the researchers' emphasis on large retailers or small chains and is based on three hypotheses focused on management practices and value generation, environmental knowledge and market orientation. This is a survey, applied to a sample of 234 employees from two retail chains, from June to October 2021, analyzed using Structural Equation Modeling (SEM), characterized as a quantitative descriptive research. The results show that subjective environmental knowledge and market orientation moderate the relationship between waste and waste management practices and the generation of value in the production chain and that the more effective, the greater the generation of value.